KONFLIK SOSIAL DALAM CERPEN PENGUNYAH SIRIH, MENJAGA PERUT DAN IKAN TERBANG KUFAH MELALUI PENDEKATAN SOSIOLOGI SASTRA - Ratna Siti Nuraeni; Hera Wahdah Humaira; Asep Firdaus (Literasi : Jurnal Bahasa dan Sastra Indonesia serta Pembelajarannya, 2020)
AbstractThis research has a goal that is focused on research into intrinsic elements and social conflict. This study is entitled "Social Conflict in Betel Chewing Short Stories, Guarding the Stomach and Flying Fish Kufa Literature Sociological Approach". Intrinsic elements in this study include the theme, plot, character and characterization, setting, and point of view. While social conflicts include forms of social conflict, causes of social conflict, and resolution of social conflicts. This study used descriptive qualitative method. The subjects of this research are by using three short stories, namely "pengunyah Sirih" by S Prsetyo Utomo, "Menjaga Perut" by Adek Alwi ", and" Ikan Terbang Kufah "by Triyanto Triwikromo. With the object of research is the intrinsic element, the form of social conflict, what causes social conflict and how to resolve social conflict. Data collection techniques used by researchers were by analyzing data from three short stories, namely "pengunyah Sirih" by S Prsetyo Utomo, "Menjaga Perut" by Adek Alwi ", and" Ikan Terbang Kufah "by Triyanto Triwikromo. In accordance with the objectives of the study, the results of this study are regarding the intrinsic element and social conflict. The form of social conflict contained in the short story namely "pengunyah Sirih" by S Prsetyo Utomo, "Menjaga Perut" by Adek Alwi ", and" Ikan Terbang Kufah "by Triyanto Triwikromo., which is about Arguing and Destruction. The cause of social conflict contained in the short story is "Pengunyah Sirih" by S Prsetyo Utomo, which is about a cow stolen by Sukro which is a slander from the Lurah to Sukro, "Menjaga Perut" the work of Adek Alwi, namely about Laila is experiencing pain and they are already longing for their three children in Jakarta, and "ikan terbang kufah" by Triyanto Triwikromo is about the Eviction and Blasting of Syeh Muso which will be blasted by Abu Abu at night for the sake of individuals. Settlement of social conflicts contained in the short story of Chewing Betel “pengunyah sirih "by S Prsetyo Utomo, namely by means of Sukro spitting on the left eye of a cow by using a painful betel leaf spit," menjaga perut "the work of Adek Alwi" resolution of social conflict by way of Abang accompany Laila on the couch the living room by accompanying Laila who was sick and waiting for news from her son, and "ikan terbang Kufah" by Triyanto Triwikromo to resolve the conflict by Kuffah throwing bombs to the bottom of the sea. Thus, theoretically the results of this study strengthen and support the theory of literary sociology, then the results of this study can be used as input for the author to further enhance the exploration of ideas by reflecting events and events in a literary work.Keywords: intrinsic element, social conflict, literary sociology.